Cognitive Style and EFL Learners’ Listening Comprehension Ability - Yousefi, Mandana (Indonesian Journal of Applied Linguistics, 2011)
Abstract     The current study aimed to investigate whether, and to what extent, there is a relationship between field independence / dependence cognitive styles and Iranian EFL learners' listening comprehension ability. For this purpose, a sample population of 131 Subjects was randomly selected.  A battery of tests including: a) the Group Embedded Figures Test (1971), b) the TOFEL listening test (1995), c) the listening task preference questionnaire, and d) the Michigan ECPE test (1996) were administered. The data analysis showed that the correlation between the TOFEL and the GEFT scores for FD learners (both males and females) was significant(r =0.70), and higher scores on the GEFT led to an increase in the FD learners TOFEL scores. Conducting one-way and two-way ANOVAs, it was suggested that while there was a relationship between cognitive style and listening comprehension (F= 18.02) and also no relationship between sex and listening comprehension (F=0.267), the interactional effect was significant (f = 7.03). Therefore, sex can be regarded as a source of performance difference in listening comprehension but not by itself and it seems that the interaction of sex and cognitive style can have a stronger effect on this skill. Regarding the learners’ preference toward the different parts of the TOEFL listening section, most  learners favored the short conversations, informal assessment, and one item/one conversation, however, the FI ones did better on the longer conversations of the second and the third parts of the TOEFL listening test. Keywords: Cognitive style, Field dependence, Field independence, Listening comprehension.